2015
DOI: 10.1177/1060028015574726
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Atrial Fibrillation Is an Independent Predictor of Mortality in Medical Intensive Care Unit Patients

Abstract: Medical ICU patients who developed new-onset AF experienced a 2-fold increase in the odds of in-hospital mortality and death at 60 days. Further research investigating contributing factors to new-onset AF and potential treatments is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…In a study investigating patients with sepsis, those who developed NOAF had a hospital mortality rate of 44% versus 22% for those who did not (9). In a study of surgical ICU patients, hospital mortality was 45% for individuals with NOAF versus 16% for those without (4). Finally, in a cohort of trauma patients, individuals with NOAF had a mortality rate two times that of those without; however, the standardized mortality ratio (observed/expected mortality by severity of illness) was similar in the two groups, suggesting that NOAF was a marker of more severe illness (10).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study investigating patients with sepsis, those who developed NOAF had a hospital mortality rate of 44% versus 22% for those who did not (9). In a study of surgical ICU patients, hospital mortality was 45% for individuals with NOAF versus 16% for those without (4). Finally, in a cohort of trauma patients, individuals with NOAF had a mortality rate two times that of those without; however, the standardized mortality ratio (observed/expected mortality by severity of illness) was similar in the two groups, suggesting that NOAF was a marker of more severe illness (10).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…The incidence of NOAF ranges from 5% to 46% (1)(2)(3). It is associated with significant morbidity and mortality (4)(5)(6), and clinicians treating patients in the intensive care unit (ICU) need to be aware of management options. Therapeutic strategies extrapolated from studies involving noncritically ill patients may not be generalizable to the critically ill; unfortunately, there are limited data from this population.…”
mentioning
confidence: 99%
“…NOAF can lead to haemodynamic instability5 and thromboembolic events 6. Critically ill patients with NOAF experience longer intensive care unit (ICU) stay, greater duration of mechanical ventilation and an increased risk of in-hospital mortality 4 7 8…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis has shown that patients with sepsis who developed new-onset AF have higher mortality (11). Studies done in the ICU have shown that critically ill patients with new-onset AF have higher mortality and longer hospital stay (12)(13)(14)(15)(16). AF is also associated with mechanical ventilator weaning failure (17).…”
Section: Discussionmentioning
confidence: 99%